LEARNIG TO BE INFORMED ON THE INTERNET: ¿ARE STUDENTS EFFECTIVE IN SEEKING AND SELECTING ONLINE INFORMATION? - María José Hernández Serrano; Marta Fuentes Agustí (Ediciones Universidad de Salamanca, 2011)
From an educational perspective, taking the Internet as an informational resource for education, the article analyzes the scope of the new information skills in regard to the concepts of literacy and information competence. This brief description of skills leads to the question of how students perform in their searching and selecting practices with online information. The main conclusions abstracted from the recent author's research are brought to debate in order to respond questions raised about the skills needed to being effective in accessing and managing online information. Finally, since the new ways to locate and operate with the information contributes to the reorganization of both the traditional models of teaching/learning and the roles of the educational stakeholders, we understand that preparing students to meet the informational demands requires of teachers as mediators or facilitators of the informational process; thus, in the final section of the article, a proposal for teaching strategies in searching and selecting online information is explored, by describing several useful activities.